A new aubergine disease caused by a whitefly‐borne strain of Tomato mild mottle virus (TomMMoV). (29th October 2012) - Dombrovsky, A.; Sapkota, R.; Lachman, O.; Pearlsman, M.; Antignus, Y.
<x xml:space="preserve">Abstract</x> The aims of the present study were to further characterize the causal agent of a new viral disease of aubergines in Israel, first observed in 2003 and tentatively named eggplant mild leaf mottle virus (EMLMV) in a previous work, and to identify the vector responsible for its spread. The disease could be transmitted mechanically from infected source plants to healthy aubergines or laboratory test plants. Transmission electron microscopy (TEM) analysis of purified virus preparations indicated the presence of viral particles with a flexible filamentous morphology (approximately 720 nm long). TEM analysis of ultrathin sections prepared from infected leaf tissue revealed the presence of cytoplasmic inclusion bodies with pinwheel and crystalline structures, typical of those induced by potyviral infection. The viral coat protein subunit was shown to have a molecular weight of 37·5 kDa by SDS‐PAGE analysis. The viral particles reacted positively in western blot analysis with an antiserum against Tomato mild mottle virus (TomMMoV) from Yemen, described as a potyvirus, vectored by the aphid Myzus persicae. The current study describes some biological properties of EMLMV and presents evidence for its transmission by the whitefly Bemisia tabaci, but not by three aphid species. The taxonomic relationship between EMLMV and TomMMoV is discussed based on their biological characteristics and sequence analysis of their genomes. It is suggested that the Israeli EMLMV should be considered a distant strain of TomMMoV, designated TomMMoV‐IL, according to the present rules of Potyviridae molecular taxonomy.